2010
DOI: 10.1111/j.1600-0501.2009.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of treatment of peri‐implant infection in animal and human studies: systematic review and meta‐analysis

Abstract: There was great heterogeneity between human and animal studies in terms of study designs and treatment procedures. Therefore, the results from this meta-analysis should be interpreted with caution. Heterogeneity between studies and its causes merit further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
(34 reference statements)
1
24
0
3
Order By: Relevance
“…The heterogeneity between animal experiments and human trials were also reported in a systematic review that compared effects of treatment of peri-implant infection between animal and humans. 28 Although larger treatment effects were found in animal experiments, definitive conclusions could not be drawn due to the heterogeneity in study designs.…”
Section: Discussionmentioning
confidence: 95%
“…The heterogeneity between animal experiments and human trials were also reported in a systematic review that compared effects of treatment of peri-implant infection between animal and humans. 28 Although larger treatment effects were found in animal experiments, definitive conclusions could not be drawn due to the heterogeneity in study designs.…”
Section: Discussionmentioning
confidence: 95%
“…One last issue should be discussed. Animal‐model studies have been used in dental research to test the safety, efficacy, and deleterious effects of periodontal and implant procedures and to understand the mechanisms of action of such events in human beings 62 . The strength of translating results from animal research to humans may be questionable; 63 however, data from animal models may be of interest when clinical and histologic outcomes must be evaluated in some specific conditions that cannot be reproduced in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, los resultados de esta metaanálisis deben interpretarse con cau-tela. La heterogeneidad entre los estudios y sus causas merecen más investigaciones (Faggion et al, 2010).…”
Section: Indicaciones De La Terapia Quirúrgica Regenerativa En Los Imunclassified